Swaps and State-Owned Enterprises in Portugal: A Story of Power, Black Swans and Illusions=Swaps e empresas públicas em Portugal: uma história de poder, cisnes negros e ilusões - Júlio Lobão (2020)
The building of narratives is one of the central elements in the functioning of modern financial markets. In this paper we analyze the discursive strategies of a group of managers of state‑owned enterprises operating in Portugal prior to the creation of that country's parliamentary committee of inquiry (CPI). This committee was established in 2013 by the Assembly of the Republic to investigate the losses resulting from the use of derivative contracts (swaps) in state‑owned enterprises. Using concepts from several scientific fields including Sociology of Finance and Cognitive Psychology, our analysis reveals that uncertainty and the managers' cognitive illusions influenced their narratives of rationalization. The power relations between the relevant social actors (public authorities, banks, firms) are also evident in the managers' discourse. In our conclusions we highlight the implications of these factors for the construction of a more contextualized view of financial relationships.